(untitled) (Environment & Health, 2022)
Objective: analysis of microbiological contamination of air in residential and public premises and determination of the content of mold fungi. Materials and methods: Saml’air Lite, manufactured by AES CHEMUNEX, France, was used to examine the indoor air (60) and public (63) for microbiological indicators (number of fungi and bacteria). Nutrient media were used: dense nutrient medium nutrient agar and dense nutrient medium Saburo agar with glucose and chloramphenicol. The obtained arithmetic mean number of colonies in each room was counted per 1 m3 of air. Statistical processing of the results was performed using the program STATISTICA 8, Microsoft Exel. Results: Microbiological, including mycological, indoor air contamination was studied. An average of 205 CFU/m3 of microscopic fungi and 1,073 CFU/m3 of mesophilic aerobic and facultative anaerobic microorganisms (QMAFAnM) were isolated in residential premises without visible signs of biodamage, which was 8,9 times and 2,5 times less respectively than in rooms with bio-damage, where the number of microscopic fungi was 1824 CFU/ m3, and QMAFAnM - 2730 CFU/m3. It was found that the air in the premises of the surveyed children’s institutions in 45,7% of cases was classified as "conditionally clean" (from 200 to 500 CFU / m3 of molds), the air "heavily polluted" was attributed to 40,0%. In office premises, 61,5% was classified as "conditionally clean" in terms of the level of mold contamination. In the air environment of "infected apartments" the presence of the number of fungi: Aspergillus srp. 7.3 times (from 11 ± 1 to 80 ± 3 CFU / m3), Cladosporium spp. – 18,9 times (from 28 ± 3 to 530 ± 24 CFU / m3), Penicillium spp. - 5.2 times (from 212 ± 14 to 1100 ± 80 CFU / m3), Mucor spr. – 5,4 times (from 13 ± 2 to 70 ± 4 CFU / m3), Acremonium spp. – 4,8 times (from 25 ± 3 to 120 ± 10 CFU / m3) and Fusarium cpp. – 4,3 times (from 21 ± 1 to 90 ± 5 CFU / m3) compared to premises without visible signs of microscopic contamination. Conclusion. According to the results of research, it was found that in the air of residential and public premises exceeded the safe level of mold in 40% of cases.